Lithium ion battery silicon-carbon negative electrode composite powder material and preparation method and production device thereof
By heating and passing silicon or carbon source gas in a vacuum state, silicon or carbon is coated on the surface of the substrate powder, the problem of difficulty in preparing nano-scale silicon-carbon negative electrode composite powder materials in the prior art is solved, and high purity is achieved , regular shape and low energy consumption preparation effect.
Patent Information
- Application Number
- CN202310989946.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult to prepare nano-scale silicon-carbon negative electrode composite powder materials in the prior art, and the preparation process has high energy consumption, and the average particle size of the generated material is micron level, and partially generates silicon carbide components.
Inert gas is introduced under vacuum to protect the substrate powder, so that the substrate powder is in a fluidized state and heated, and the silicon source gas or carbon source gas is introduced. Silicon or carbon is coated on the surface of the substrate powder to obtain nano-scale silicon-carbon negative electrode composite powder Material. The heating temperature of this method does not exceed 700°C, and the energy consumption is low. The oxidation reaction is suppressed by vacuum evacuation during the preparation process.
The prepared silicon-carbon negative electrode composite powder material has nanometer-level particle size, regular powder shape, high purity, good surface coating consistency, strong binding force, and low energy consumption.
Smart Images

Figure CN119461337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of silicon-carbon negative electrode materials, in particular to a lithium ion battery silicon-carbon negative electrode composite powder material and a preparation method and a production device thereof. Background Art
[0002] The Chinese patent with publication number CN107887582B discloses a silicon / carbon powder composite material and its preparation method and battery negative electrode material; the preparation method of the silicon / carbon powder composite material is to prepare silicon slurry by vacuum heating and melting silicon to a molten state, and then to pass a mixed gas of nitrogen and carbon source gas into the silicon slurry, and to perform close-coupled ultrasonic vacuum gas atomization to prepare the silicon / carbon powder composite material. The preparation method requires heating silicon to a molten state at above 1500°C to prepare silicon slurry, and it needs to be sprayed through an atomizing nozzle, which consumes very high energy. The average particle size of the silicon / carbon powder composite material obtained by the preparation method is micron-level, and a part of the silicon carbide component is generated. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a lithium-ion battery silicon-carbon negative electrode composite powder material and a preparation method and production device thereof in view of the shortcomings of the prior art, so as to obtain a nano-scale silicon-carbon negative electrode composite powder material with regular powder shape, high purity, strong interface bonding between the surface coating material and the basic powder, good coating consistency and low energy consumption.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a lithium-ion battery silicon-carbon negative electrode composite powder material, comprising the following steps:
[0005] In a vacuum state, an inert gas is introduced to protect the base powder, so that the base powder is in a fluidized state and heated, and a silicon source gas or a carbon source gas is introduced, and the heating temperature is higher than the cracking temperature of the silicon source gas or the carbon source gas. After the silicon source gas or the carbon source gas is cracked, silicon or carbon is coated on the surface of the base powder;
[0006] When the base powder is carbon powder, the gas introduced is silicon source gas;
[0007] When the base powder is silicon powder, the gas introduced is a carbon source gas.
[0008] The heating temperature used in the present invention only needs to be higher than the cracking temperature of the silicon source gas or the carbon source gas, and the heating temperature does not exceed 700 degrees Celsius. The energy consumption is low, and a nano-scale silicon-carbon negative electrode composite powder material is obtained to achieve a uniform coating effect.
[0009] The present invention firstly performs vacuuming to reduce the oxygen concentration in the working area, effectively inhibits the oxidation reaction of the material during the treatment process, and reduces the oxygen content of the material.
[0010] As one of the concepts of the present invention, the present invention is used for the modified production of silicon-carbon negative electrode composite powder materials for lithium-ion batteries, using SiH4 gas containing a silicon source, through heating and cracking decomposition, to carry out fluidized carbon coating of carbon powder to obtain a composite silicon-carbon negative electrode material.
[0011] Nano-silicon cracking process: SiH4=2Si+2H2↑
[0012] As the second concept of the present invention, the present invention is used for the modified production of silicon-carbon negative electrode composite powder materials for lithium-ion batteries, and utilizes carbon-containing sources such as CH4, C2H2, etc., to heat and crack and decompose, and then fluidize the carbon to coat the silicon powder to obtain a composite silicon-carbon negative electrode material.
[0013] Nanocarbon cracking process: C2H6=2C+3H2↑
[0014] CH4=C+2H2↑
[0015] Preferably, the inert gas is nitrogen or argon.
[0016] In a preferred embodiment of the present invention, the step of fluidizing the matrix powder comprises introducing the matrix powder from the top of the reaction chamber and introducing nitrogen from the bottom of the reaction chamber, with a nitrogen flow rate of 3-6 Nm 2 / h, the base powder is put into fluidized state under the action of nitrogen.
[0017] The present invention introduces a certain flow of nitrogen to make the base powder in a fluidized state. The nitrogen flow is used to achieve fluidization and suspension of the powder in the working area during the coating process to achieve a uniform coating effect.
[0018] In a preferred embodiment of the present invention, the matrix powder and the cracked products of the silicon source gas or the carbon source gas are continuously circulated, and the reaction time is 6.5-12 hours.
[0019] The coating layer thickness is controlled by the coating gas flow rate, reaction chamber temperature and coating process time. The coating silicon source gas flow rate range is 0.25-2.0Nm 3 / h, the coating carbon source gas flow range is 0.2-3.0Nm 3 / h.
[0020] In a preferred embodiment of the present invention, the particle size of the matrix powder is in the range of 10-100 nm.
[0021] In a preferred embodiment of the present invention, the heating temperature is 550-650°C, the heating power is 40-80kw, and the heating time is 1-3h, so that Sih4 and CH4 are cracked at the heating temperature.
[0022] In a preferred embodiment of the present invention, when the base powder is carbon powder, the mass of a single batch of processed powder is 100-300 kg.
[0023] The invention also discloses a lithium ion battery silicon-carbon negative electrode composite powder material prepared by the preparation method, the powder has a regular shape, high purity, strong interface bonding between the surface coating material and the basic powder, good coating consistency and low energy consumption.
[0024] The present invention also discloses a production device for silicon-carbon negative electrode composite powder materials for lithium-ion batteries, comprising a reaction furnace body, a matrix powder feeding port, a composite powder receiving port, an air inlet and an air outlet respectively arranged on the reaction furnace body, a heating module is provided at the lower part of the reaction furnace body, and the device also comprises a fan impeller and a fluidized bed arranged at the bottom of the reaction furnace body, the fluidized beds are respectively arranged on both sides of the fan impeller, a vertically arranged flow channel pipe is provided above the fan impeller, a guide is provided above the flow channel pipe, an inner cavity of the flow channel pipe forms an ascending channel, and a reflux channel is formed between the outer wall of the flow channel pipe and the inner wall of the reaction furnace body.
[0025] The powder circulates in the hot reaction zone to achieve uniform coating. The key components for fluidized circulation are the flow tube, fluidized bed, and fan impeller. The fan impeller blows out nitrogen. The nitrogen flow rate and fan impeller speed need to be adjusted according to the different particle sizes of the powder. Both are used to achieve fluidization and suspension of the powder in the working area during the coating process.
[0026] The reflux channel formed between the outer wall of the flow channel tube and the inner wall of the reaction furnace body means forming an ascending channel, and circulating flow with the ascending channel.
[0027] In a preferred embodiment of the present invention, the matrix powder in the matrix powder feed port is transported by nitrogen, and the nitrogen pressure is 0.1-0.3 MPA.
[0028] In a preferred embodiment of the present invention, a matrix powder feed port is opened on the upper side wall of the reaction furnace body.
[0029] The upper part of the reaction furnace body is the cold end, and the lower part is the effective heating area. The matrix powder feed port is opened at the cold end of the reaction furnace body, taking into account the service life and stability of the seal. If it is connected to the hot end, the seal and the opening and closing of the furnace shell cannot be achieved.
[0030] In a preferred embodiment of the present invention, the composite powder receiving port is arranged at the bottom of the reaction furnace body.
[0031] In a preferred embodiment of the present invention, the air outlet is arranged at the top of the reaction furnace body, and a filter is installed at the air outlet.
[0032] The particle size of the filtered powder is submicron and nanometer, and the yield of the composite powder is improved after filtering.
[0033] In a preferred embodiment of the present invention, the air inlet is arranged at the bottom of the reaction furnace body, below the fan impeller.
[0034] Since the gas density is light, the gas will float along the air flow direction when heated when entering the reaction chamber and will be cracked in the reaction chamber, so the air inlet is arranged at the bottom of the reaction furnace body.
[0035] In a preferred embodiment of the present invention, the diameter of the upper end of the reaction furnace body is greater than the diameter of the lower end.
[0036] In a preferred embodiment of the present invention, the heating module is installed on the outer wall of the reaction furnace body.
[0037] In a preferred embodiment of the present invention, the heating module is also equipped with a heat preservation module.
[0038] The overall dimensions of the reactor body are: 2-4m in length, 4-6m in width, and 3-5m in height.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The powder compactness and bulk density increase.
[0041] (2) High purity and good surface coating consistency.
[0042] (3) The heating temperature and cooling speed are controllable.
[0043] (4) The morphology is improved and the powder shape is regular.
[0044] (5) The powder is dynamically dispersed in the reaction zone to avoid powder agglomeration. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a schematic structural diagram of a production device for silicon-carbon negative electrode composite powder material for lithium-ion batteries in one embodiment of the present invention.
[0046] Figure 2 This is an electron microscope image of a lithium-ion battery silicon-carbon negative electrode composite powder material prepared in one embodiment of the present invention.
[0047] Among them, 1 is the reaction furnace body, 2 is the guide, 3 is the flow channel pipe, 4 is the high-pressure air pipe, 5 is the fan impeller, 6 is the fluidized bed, 7 is the driving motor, 8 is the working area, 9 is the heating module, 10 is the filter, 11 is the air outlet, 12 is the matrix powder feeding port, 13 is the composite powder receiving port, 14 is the air inlet, and 15 is the insulation module. DETAILED DESCRIPTION
[0048] Example 1
[0049] like Figure 1 As shown, a production device for silicon-carbon negative electrode composite powder material of lithium-ion battery includes a reaction furnace body 1, and a matrix powder feed port 12 is opened on the upper side wall of the reaction furnace body 1. The composite powder receiving port 13 is arranged at the bottom of the reaction furnace body 1. The air outlet 11 is arranged at the top of the reaction furnace body 1, and a filter 10 is installed at the air outlet 11. A heating module 9 is arranged at the lower part of the reaction furnace body 1, and the heating module 9 is installed on the outer wall of the reaction furnace body 1. The heating module 9 is also installed with a heat preservation module 24. The production device also includes a fan impeller 5 and a fluidized bed 6 arranged at the bottom of the reaction furnace body 1, and the fluidized bed 6 is respectively arranged on both sides of the fan impeller 5. A vertically arranged flow channel 3 is arranged above the fan impeller 5, and a flow guide 2 is arranged above the flow channel 3. The inner cavity of the flow channel 3 forms an ascending channel, and a reflux channel is formed between the outer wall of the flow channel 3 and the inner wall of the reaction furnace body 1. The middle area of the flow channel 3 is a working area 8. The diameter of the upper end of the reaction furnace body 1 is greater than the diameter of the lower end. The overall dimensions of the reaction furnace body are: 2.5m long, 4m wide, and 3m high.
[0050] The preparation method of lithium-ion battery silicon-carbon negative electrode composite powder material comprises the following steps:
[0051] a. The entire reactor body is pre-evacuated to a vacuum degree of 0.1 Pa to reduce the oxygen content in the reactor body.
[0052] b. The matrix powder carbon powder enters the working area 8 in the reaction furnace body 1 through the matrix powder feed port 12. The weight of a single batch of matrix powder carbon powder is 3KG. It is transported by nitrogen positive pressure with a nitrogen pressure of 0.1MPA. The particle size of the matrix powder carbon powder is 30nm.
[0053] c. Start the heating module 9 of the reactor body 1 to heat the working area 8. The heating temperature is 650°C, the heating time is 2 hours, and the reactor heating power is 60kW. Nitrogen is introduced from the gas pipe 4 at the bottom of the working area 8, and the nitrogen flow rate is 4.5Nm 2 / h, start the fluidized bed 6 function and the fan impeller 5, the impeller speed is 80-130r / min, let the carbon powder into the fluidized state, and introduce the process gas SiH4 from the gas pipe 4 at the bottom of the working area 8 in the reactor body 1, and the silicon source gas flow rate is 2.0Nm 3 / h. SiH4 is cracked in the lower heating section of the working area 8 to generate a single Si source.
[0054] d. Driven by the fan impeller 5, a mixture of carbon powder, elemental Si source, SiH4 and nitrogen is introduced into the flow channel tube 3 from the lower end thereof, flows upward, flows out through the upper end of the flow channel tube 3, and flows from the upper part to the lower part through the channel between the flow channel tube 3 and the working area 8, and enters the fan impeller 5, and is introduced into the flow channel tube 3 from the lower end thereof again. The rotation speed of the fan impeller 5 can be adjusted according to the production process requirements.
[0055] e. During the upward and downward directional circulation of the carbon powder in the working area 8, the Si source generated by the cracking of the heated SiH4 is continuously deposited on the surface of the carbon powder to form a composite silicon-carbon negative electrode powder material with a C@Si core-shell structure. The reaction time is 6.5 h.
[0056] f. The remaining nitrogen and hydrogen in the production process are controlled by the equipment system pressure control module according to the pressure detection control of the equipment system, pass through the powder filter 10 in the working area 8, and then pass out of the reaction furnace body.
[0057] g. After completing the production according to the production process requirements, stop introducing the process gas SiH4 and nitrogen, stop heating, and the cooled composite silicon-carbon negative electrode powder material product is sent out by nitrogen positive pressure.
[0058] The tap density of the composite silicon-carbon negative electrode powder material product prepared in this embodiment is 0.21 g / cm 2 The powder particle size is 30-90 nm. The composite silicon-carbon negative electrode powder material prepared in this embodiment is as follows Figure 2 As shown, the morphology is improved, the powder shape is regular, the surface coating consistency is good, and the powder is dynamically dispersed in the reaction zone. The composite silicon-carbon negative electrode powder material product prepared in this embodiment is tested for performance, and the first discharge capacity is 3200mAh / g, and the first efficiency is 88.04%.
[0059] The production process of carbon-coated silicon composite silicon-carbon negative electrode powder material is the same as that in Example 1, except that the precursor is silicon or silicon oxide powder, and the process gas selected is one of CH4, C2H2, etc., to produce Si@C or SiO@C composite silicon-carbon negative electrode powder material.
Claims
1. A method for preparing a lithium-ion battery silicon-carbon negative electrode composite powder material, characterized in that The following steps are involved: In a vacuum state, an inert gas is introduced to protect the base powder, so that the base powder is in a fluidized state and heated, and a silicon source gas or a carbon source gas is introduced, and the heating temperature is higher than the cracking temperature of the silicon source gas or the carbon source gas. After the silicon source gas or the carbon source gas is cracked, silicon or carbon is coated on the surface of the base powder; When the base powder is carbon powder, the gas introduced is silicon source gas; When the base powder is silicon powder, the gas introduced is a carbon source gas.
2. The method for preparing the silicon-carbon negative electrode composite powder material for lithium ion batteries according to claim 1, characterized in that: The step of fluidizing the matrix powder includes introducing the matrix powder from the top of the reaction chamber and introducing nitrogen from the bottom of the reaction chamber, with a nitrogen flow rate of 3-6 Nm 2 / h, the base powder is put into fluidized state under the action of nitrogen.
3. The method for preparing the lithium ion battery silicon-carbon negative electrode composite powder material according to claim 1, characterized in that: The products after cracking of the matrix powder and the silicon source gas or the carbon source gas are continuously circulated, and the reaction time is 6.5-12 hours.
4. The method for preparing the silicon-carbon negative electrode composite powder material for lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The particle size of the matrix powder ranges from 10nm to 100um.
5. The method for preparing the silicon-carbon negative electrode composite powder material for lithium ion batteries according to any one of claims 1 to 3, characterized in that: The heating temperature is 550-650℃, the heating power is 40-80kw, and the heating time is 1-3h.
6. A lithium-ion battery silicon-carbon negative electrode composite powder material prepared by the preparation method described in any one of claims 1 to 5, the powder having a regular shape, high purity, strong interface bonding between the surface coating material and the basic powder, good coating consistency, and low energy consumption.
7. A production device for lithium-ion battery silicon-carbon negative electrode composite powder material, comprising a reaction furnace body (1), a matrix powder feed inlet (12), a composite powder receiving inlet (13), an air inlet (14) and an air outlet (11) are respectively arranged on the reaction furnace body (1), and a heating module (9) is arranged at the lower part of the reaction furnace body (1), characterized in that: It also includes a fan impeller (5) and a fluidized bed (6) arranged at the bottom of the reaction furnace body (1), the fluidized bed (6) being arranged on both sides of the fan impeller (5), a vertically arranged flow channel tube (3) being arranged above the fan impeller (5), a flow guide (2) being arranged above the flow channel tube (3), an inner cavity of the flow channel tube (3) forming an ascending channel, and a reflux channel being formed between the outer wall of the flow channel tube (3) and the inner wall of the reaction furnace body (1).
8. The production device of lithium-ion battery silicon-carbon negative electrode composite powder material according to claim 7, characterized in that: The matrix powder feed port (12) is opened on the upper side wall of the reaction furnace body (1).
9. The production device of lithium-ion battery silicon-carbon negative electrode composite powder material according to claim 7, characterized in that: The composite powder receiving port (13) is arranged at the bottom of the reaction furnace body (1).
10. The production device of lithium-ion battery silicon-carbon negative electrode composite powder material according to claim 7, characterized in that: The air outlet (11) is arranged at the top of the reaction furnace body (1), and a filter (10) is installed at the air outlet (11).
Citation Information
Patent Citations
A silicon / carbon powder composite material, its preparation method, and a battery anode material
CN107887582B
Cited By
Preparation method and application of nanoscale lithium-silicon alloy
CN121156290A